Socioeconomic status and equity among patients with cardiogenic shock - Marcos-Mangas, Marta; López-Sobrino, Teresa; Ariza-Solé, Albert; Rueda-Sobella, Ferran; Sanz-Girgas, Esther; Aboal, Jaime; Pastor, Pablo; Buera, Irene; Sionis, Alessandro; Andrea, Rut; Rodríguez-López, Judit; Tomas, Carlos; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundWe aimed to analyze the impact of socioeconomic status (SES) on management and in-hospital outcomes of patients with cardiogenic shock (CS).MethodsThis was a prospective observational registry conducted (December 2018–November 2019) in Intensive Cardiac Care Units (ICCU) across 8 tertiary care centers. Consecutive patients aged ≥18 years with a primary diagnosis of cardiogenic shock were included. SES was defined using a numerical index that incorporates mean income levels, premature mortality, and avoidable hospitalizations observed within a specific health area. SES values were categorized into tertiles. In-hospital procedures, complications, length of stay, and in-hospital mortality were collected.ResultsA total of 382 patients were included (mean age: 65.3 years). There were no differences in age, sex, or major comorbidities across SES groups. CS was more frequently due to acute coronary syndrome (ACS) in patients with low SES (66.9% vs. 58%, p = 0.022). No significant differences were observed regarding SCAI stage or other severity markers of CS across SES groups. Patients with low SES were more likely to receive pulmonary artery catheterization (p = 0.029) and mechanical circulatory support (p = 0.038). After adjusting for potential confounders, clinical management was similar regardless SES. Lower SES patients exhibited a higher incidence of bleeding (p = 0.018). There were no differences in length of stay or in-hospital mortality among SES groups.ConclusionsBeyond a higher rate of ACS-related CS, patients with low SES exhibited a clinical profile and shock severity comparable to other SES groups. Therapeutic management aligned with guideline recommendations even in patients with low SES.